2022
DOI: 10.1093/gbe/evac151
|View full text |Cite
|
Sign up to set email alerts
|

Expansion and Neofunctionalization of Actinoporin-like Genes in Mediterranean Mussel (Mytilus galloprovincialis)

Abstract: Pore-forming toxins are an important component of the venom of many animals. Actinoporins are potent cytolysins that were first detected in the venom of sea anemones; however, they are occasionally found in animals other than cnidarians and are expanded in a few predatory gastropods. Here, we report the presence of 27 unique actinoporin-like genes with monophyletic origin in Mytilus galloprovincialis, which we have termed mytiporins. These mytiporins exhibited a remarkable level of molecular diversity and gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 111 publications
0
1
0
Order By: Relevance
“…Phylogenetically, the MPEG1 in invertebrate are distant from that in vertebrates, implying diversified evolution of MPEG1 in invertebrate and vertebrate. Previous works have shown that the innate immune genes, such as TLR, NLR, and the pore-forming toxin actinoporin, are prone to expansion and duplication in invertebrate, as a compensation for the lack of adaptive immunity [34] , [35] , [36] . For MPEG1, its duplication in Euteleostomi led to the emergence of perforin-1 [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetically, the MPEG1 in invertebrate are distant from that in vertebrates, implying diversified evolution of MPEG1 in invertebrate and vertebrate. Previous works have shown that the innate immune genes, such as TLR, NLR, and the pore-forming toxin actinoporin, are prone to expansion and duplication in invertebrate, as a compensation for the lack of adaptive immunity [34] , [35] , [36] . For MPEG1, its duplication in Euteleostomi led to the emergence of perforin-1 [37] .…”
Section: Discussionmentioning
confidence: 99%